The Effectiveness of Cooperative and Conventional Physical education Models and the Availability of Facilities for Physical education Management - Nita Peranita; Kadek Yogi Parta Lesmana; I Made Satyawan (Journal of Physical Education Health and Sport, 2025)
The traditional model of physical education, where the teacher is often central to the process, on the contrary, involves more knowledge transfer and organized instructions of a teacher. Although this model might prove to be efficient in delivering a high collection of information to students, it might limit the student interaction and decreasing reflective physical education. Access to physical education amenities is one of the determinants of the success of the two models. Digital tools, proper classrooms, physical education media, and the availability of resources can all be used to positively influence motivation and practical physical education experiences as well as support diverse instruction methods. It has been theorized in literature that cooperative physical education is more likely to succeed when the facilities are oriented to group work as opposed to the very likely success of conventional physical education in environments where teacher control and direct instruction are important. For the effectiveness of any model, consequently, there is not only the design of instruction but also the physical education environment in which the implementation of the model takes place. In general, the literature results suggest that the cooperative physical education tends to create more active and cooperative physical education experiences whereas the traditional physical education is still valuable when delivering formal knowledge. To achieve the management of physical education optimization and enhance educational performance, it is important to ensure that facilities are sufficient and well aligned with the selected model.